EFFECTIVENESS OF TRIMEBUTINE MALEATE FOR COMPREHENSIVE TREATMENT OF CHRONIC PANCREATITIS IN CHILDREN - I. S. Lembrik (Union of pediatricians of Russia, 2014)
Relevance. Pancreatic pathology is often observed in children, especially in adolescents. Timely adequate therapy helps to reduce duration of hospitalization and, possibly, prevent future relapses. The study was aimed at examining peculiarities of the course of chronic pancreatitis in children and determine effectiveness of comprehensive treatment using trimebutine maleate. Patients and methods. 100 children aged 7-18 years with chronic pancreatitis were examined. The control group was comprised of 30 virtually healthy children of the similar age. Results. According to the anamnestic data, eating disorder (68.0%), pancreatic exacerbation of chronic noncalculolis cholecystitis or sphincter of Oddi dysfunction (65.0 and 50.0%, respectively) are significant risk factors of chronic pancreatitis in children; obesity (40.0%) and hypodynamia (35.0%) are less common risk factors. The main clinical manifestations of chronic pancreatitis are "girth half" spastic abdominal pain attacks (78.0%), nausea regardless of food intake (65.0%) and bile emesis not attenuating the patient's condition (45.0%). The study established moderate manifestations of exocrine pancreatic failure. The vasointestinal polypeptide level was low at erosive lesion of gastroduodenal zone's mucosa (2.15 ± 0.3 ng/l) and cardiac esophageal sphincter failure (2.29 ± 0.2 ng/l). Regression of clinical manifestations was more rapid in the group of children taking a motility regulator - trimebutine maleate - than in the group of children, who did not take this drug. Conclusion. It is necessary to identify and control risk factors in order to prevent development of chronic pancreatitis. Introduction of a motility regulator - trimebutine maleate - into the comprehensive therapeutic program is effective and helps to reduce duration of hospitalization.